2018
DOI: 10.4102/hsag.v23i0.1097
|View full text |Cite
|
Sign up to set email alerts
|

The role of triage to reduce waiting times in primary health care facilities in the North West province of South Africa

Abstract: Background: Worldwide, patients visiting health care facilities in the public health care sector have to wait for attention from health care professionals. In South Africa, the Cape Triage Score system was implemented successfully in hospitals’ emergency departments in the Cape Metropole. The effective utilisation of triage could improve the flow of primary health care (PHC) patients and direct the patients to the right health care professional immediately.Aim: No literature could be traced on the implementati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Furthermore, limited access to affordable healthcare services is an important contributor to late ANC presentation in African countries [18]. Even in South Africa, where patients are no more than a ten minute walking distance from a Primary Health Care Centre (PHC), long waiting periods, overcrowding and limited health personnel continue to challenge the provision of quality health services [19, 20]. Ebonwu et al (2018) found that late ANC presentation in rural South Africa was associated with being married, employed, less than 20 years of age, having an unplanned pregnancy and being pregnant for the first time [18].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, limited access to affordable healthcare services is an important contributor to late ANC presentation in African countries [18]. Even in South Africa, where patients are no more than a ten minute walking distance from a Primary Health Care Centre (PHC), long waiting periods, overcrowding and limited health personnel continue to challenge the provision of quality health services [19, 20]. Ebonwu et al (2018) found that late ANC presentation in rural South Africa was associated with being married, employed, less than 20 years of age, having an unplanned pregnancy and being pregnant for the first time [18].…”
Section: Introductionmentioning
confidence: 99%
“…Women usually delayed presenting to the clinic not only because of home management, but because of protracted clinic waiting times and bottle necks (Egbujie et al, 2018;Sastry et al, 2015;Stime et al, 2018;Swart et al, 2018). As many women explained, it seemed pointless to present to the clinic and wait for some hours, with no resolution at the end of the day: "You'd rather try helping yourself at home, rather than coming to the clinic".…”
Section: Methodsmentioning
confidence: 99%
“…Triage (broadly defined as the process of prioritising patients for care based on their needs) [54] has also been shown to reduce waiting times in a hospital in South Africa, though it was less effective when used in two PHC clinics. [55,56] Effective triage can be challenging and resource-intensive to sustain, [57] and sub-optimal implementation of symptom-based triage for TB IPC has been documented by several studies. [58][59][60][61] Active queue management has also been tested: a qualitative study around the use of a 'Fast Queue' in clinics in KZN found that the use of multiple, managed queues was generally well-received by attendees, particularly if accompanied by smooth (i.e., unidirectional) flow and effective communication with HCWs, though there were still those who experienced long waiting times.…”
Section: Potential Interventionsmentioning
confidence: 99%